SPEN is required for Xist upregulation during initiation of X chromosome inactivation - Teresa Robert-Finestra (Nature Portfolio, 2021)
SPEN is a key player in initiation of X chromosome inactivation. Here, the authors show that SPEN is required for Xist-mediated silencing of its own antisense regulator Tsix.